Wind power : the industry grows up - Busby, Rebecca L. (PennWell Corp., 2012)
In her timely new book, best-selling author Rebecca Busby provides a balanced, comprehensive view of the wind power industry: "required reading for people who want to obtain an initial overview of this most interesting energy field." The book enables readers to: Expand their knowledge of the environmental and economic issues associated with wind power development Understand the steps involved in developing a wind farm and the best ways to operate it successfully and profitably; Find out how wind energy is integrated into power grids and transmission networks, including the growing use of technologies for energy storage; Get an overall picture of the global wind business and the deployment of offshore wind power; Learn the basics of how wind power is generated and used, how wind turbines work, and how wind power systems are designed; Understand how wind energy is measured and evaluated at prospective sites with included maps of wind resources worldwide; Review the status of global wind energy research, technology development, and product testing, as well as advanced wind power generation concepts. --